Invazivna tujerodna vrsta veliki pajesen (Ailanthus altissima) v Sloveniji - Jerman, Jan (Varstvo narave, 2025)
Tree of heaven (Ailanthus altissima (Mill.) Swingle) is an invasive alien plant species that originates from China. The species is on the list of invasive alien species of Union concern in accordance with Regulation (EU) No 1143/2014. It is widespread in Slovenia, with a denser population in the Karst region, Prekmurje region as well as the central Slovenia region. Due to its rapid growth, large number of seeds and allelopathic effects, it quickly overgrows native vegetation, degrades habitats and threatens biodiversity and ecosystem functioning. It threatens mainly dry grasslands, forest edges, riparian zones and urban green areas, where it displaces native plants and changes soil properties. Mechanical removal, long-term monitoring of its distribution and development of new effective and environmentally acceptable control methods can slow or stop its spread. The use of synthetic herbicides in the natural environment is prohibited by law in Slovenia, so we primarily deal with the tree of heaven by pulling, girdling and felling. Another promising measure is the new bioherbicide Ailantex, which acts on the basis of a virulent fungus of the genus Verticilium that causes wilting of the tree of heaven, but its use in Slovenia has not yet been approved.
Keywords: Ailanthus altissima; invasive alien species; invazivne tujerodne vrste; management methods; metode obvladovanje; metode odstranjevanja; monitoring; Natura 2000; removal methods; varstvo narave